2016
DOI: 10.1007/s40256-016-0189-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Stroke and Bleeding with Rivaroxaban and Dabigatran in Atrial Fibrillation: Analysis of the US Medicare Part D Data

Abstract: There was no difference in stroke prevention between rivaroxaban and dabigatran; however, rivaroxaban was associated with a higher risk of thromboembolic events other than stroke, death, and bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 26 publications
0
34
1
8
Order By: Relevance
“…Although underdosing of apixaban was associated with an increased risk of stroke, dabigatran 75mg and rivaroxaban 10mg/15mg use in patients without a renal indication was not associated with differences in stroke or major bleeding rates [16]. A sub-therapeutic effect may be plausible for low dose rivaroxaban in our study, with an ischemic stroke rate well in excess of previous studies [89, 3234]. Although we did not have laboratory values to estimate renal function and determine if dosing was appropriate, ischemic stroke and bleeding rates were low (0 events) among low dose rivaroxaban users with diagnosed CRI.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Although underdosing of apixaban was associated with an increased risk of stroke, dabigatran 75mg and rivaroxaban 10mg/15mg use in patients without a renal indication was not associated with differences in stroke or major bleeding rates [16]. A sub-therapeutic effect may be plausible for low dose rivaroxaban in our study, with an ischemic stroke rate well in excess of previous studies [89, 3234]. Although we did not have laboratory values to estimate renal function and determine if dosing was appropriate, ischemic stroke and bleeding rates were low (0 events) among low dose rivaroxaban users with diagnosed CRI.…”
Section: Discussioncontrasting
confidence: 44%
“…When used for secondary stroke prevention at standard doses, dabigatran and rivaroxaban have been reported to have similar risk for thromboembolic events, bleeding events, and all-cause mortality based upon indirect treatment comparisons using trial data [67]. Recent observational studies focused on patients treated for primary prevention have, however, suggested an increased risk of bleeding and mortality with rivaroxaban at both the renal (75mg dabigatran, 15mg rivaroxaban) and standard doses (150mg dabigatran, 20mg rivaroxaban) [89]. Single-center studies of DOACs post-stroke have described variability in recurrence risk and recurrent stroke volume for rivaroxaban, dabigatran, and apixaban [1011].…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth cohort of GARFIELD AF, more than 70% of AF patients are anticoagulated, with a growing proportion being initiated on NOAC therapy over warfarin (37%), and OAC use was associated with a 35% lower risk of death 77 . Other registry data have since been published for comparative effectiveness and safety data for dabigatran, rivaroxaban, apixaban, and warfarin 50, 78, 79 .…”
Section: How Do Clinical Trial Results Compare With “Real World Data”?mentioning
confidence: 99%
“…Подобные закономерности были выявлены и в другом анализе пациентов Medicare, проведенном I. Hernandez и Y. Zhang [11]. В данном исследовании при среднем периоде наблюдения около 1 года у пациентов, получавших дабигатран в дозе 150 мг 2 раза/сут.…”
Section: Expert Board Resolutionunclassified